Assessment of changes in concentrations of selected criteria pollutants in the Vaal and Highveld Priority Areas - Feig, Gregor; Garland, Rebecca M.; Naidoo, Seneca; Maluleke, Amukelani; Van der Merwe, Marna (Clean Air Journal, 2019)
Ambient air pollution has important impacts on a variety of environmental issues, particularly on human health and ecosystem processes. A key tool for understanding the impacts of atmospheric pollution is through the long term measurement of the ambient concentrations of criteria atmospheric pollutants. Monitoring of ambient pollution concentrations has been conducted in the National Air Quality Priority areas since 2009. During this time period, significant changes in the management of air pollution have occurred, including the adoption of the ambient air quality standards, and the implementation of section 21 emission standards. This paper examines the long term evolution of ambient concentrations for PM, SO2 in the Vaal Triangle Airshed Priority Area 2007-2017 and Highveld Priority Area. These trends will be evaluated against the implementation of management interventions and highlight the variation in the measured concentrations and emerging areas of concern.